2011
DOI: 10.1097/sla.0b013e318216f56e
|View full text |Cite
|
Sign up to set email alerts
|

Operative Outcomes Beyond 30-day Mortality

Abstract: The effects of older age extend to other important outcome measures after CRC procedures beyond operative mortality. As one of the largest multihospital studies, our study identified increased morbidity in the oldest old, a growing population. Our results should stimulate review of current policy and resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 21 publications
5
37
1
Order By: Relevance
“…While the numerical difference is large, both data is insignificant at p=0.071 and p=0.392 respectively. This finding contradicts previous literature, whereby age has inevitably been identified as a risk factor for longer LOS and in needing higher postoperative care (13)(14)(15). However, caution must be exercised in the analysis of this data as the small study sample size could be limiting the analysis.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…While the numerical difference is large, both data is insignificant at p=0.071 and p=0.392 respectively. This finding contradicts previous literature, whereby age has inevitably been identified as a risk factor for longer LOS and in needing higher postoperative care (13)(14)(15). However, caution must be exercised in the analysis of this data as the small study sample size could be limiting the analysis.…”
Section: Discussioncontrasting
confidence: 85%
“…Similarly, there were no differences in both the 30-day and 90-day postoperative mortality, p=0.269 and p=0.565 respectively, which was not observed before in previous literature (14,(16)(17)(18).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…30, 41, 42 We also could not measure preoperative physical status, which is associated with 30-day mortality. 30, 4144 …”
Section: Discussionmentioning
confidence: 99%
“…Al-Refaie et al 5 studied patients over 80 years of age undergoing colorectal surgery and found elderly patients to be prone to major complications (17%), prolonged length of stay (29%) and increased risk of 30-day mortality (6%). In their study, multivariable analysis demonstrated that older age independently predicted worse postoperative outcomes in the oldest old.…”
Section: Discussionmentioning
confidence: 99%